Living with lower productivity growth: Impact on exports - Filippo Di Mauro; Bernardo Mottironi; Gianmarco Ottaviano; Alessandro Zona-Mattioli (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
This paper investigates the impact of sustained lower productivity growth on exports, by looking at the role of the productivity distribution and allocative efficiency as drivers of export performance. It follows and goes beyond the work of Barba Navaretti et al. (2017), analysing the effects of productivity on exports depending on the dynamics of allocative efficiency. Low productivity growth is a well-documented stylised fact in Western countries - and possibly a reality likely to persist for some time. What could be the impact of persistent sluggish growth of productivity on exports? To shed light on this question, this paper examines the relationship between the productivity distribution of firms and sectoral export performance. The structure of firms within countries or even sectors matters tremendously for the nexus between productivity and exports at the macroeconomic level, as the theoretical and empirical literature documents. For instance, whether too few firms at the top (lack of innovation) or too many firms at the bottom (weak market selection) drives slow average productivity at the macro level has very different implications and therefore demands different policy responses.
urn:nbn:de:gbv:3:2-97153
Keywords: 330; productivity; exports